Odpowiedzi

2010-04-05T20:09:57+02:00
√6*√1/6= 6^½ * 6^-½ = 6⁰ = 1

√0.4*√10= (0,4)^½ * 10^½ = (0,4*10)^½ = 4^½ = √4 = 2

√(1⅕) * √0,3 = √(1,2*0,3) = √0,36 = 0,6

∛2 * ∛4= ∛(2*4) = ∛8 = 2

∛0.08*∛100= ∛(0,08*100) = ∛8 = 2

∛(2/9) * ∛1⅓ = ∛[(2/9) * (4/3) ] = ∛(8/27) = ⅔

√0.9:√10 = √(0,9:10) = √0,09 = 0,3

∛10000:∛10= ∛(10000:10) = ∛1000 = 10
Najlepsza Odpowiedź!
2010-04-05T20:11:28+02:00
(wystarczu to wziąść pod jeden pierwiastek)

a)√6*√1/6=√6*1/6 =√1=1
b)√0.4*√10=√0,4*10=√4 =2
c)√1 i1/5*√0.3=√1 i 1/5*0,3=√1,2*0,3=√0,36=6
d)∛2*∛4=∛2*4=∛8=2
e)∛0.08*∛100=∛0,08*100=∛8=2
f)∛2/9*∛1i1/3=∛2/9*1i1/3=∛2/9*4/3=∛2/9*12/9=∛24/9=∛2i6/9
g)√0.9:√10=√0,9:10=√0,09=0,3
h)∛10000:∛10=∛10000:10=∛1000=10

:P